Crystallinity dynamics of gold nanoparticles during sintering or coalescence. Issue 2 (22nd December 2015) - Goudeli, Eirini; Pratsinis, Sotiris E.
Abstract : The crystallinity of gold nanoparticles during coalescence or sintering is investigated by molecular dynamics. The method is validated by the attainment of the Au melting temperature that increases with increasing particle size approaching the Au melting point. The morphology and crystal dynamics of nanoparticles of (un)equal size during sintering are elucidated. The characteristic sintering time of particle pairs is determined by tracing their surface area evolution during coalescence. The crystallinity is quantified by the disorder variable indicating the system's degree of disorder. The atoms at the grain boundaries are amorphous, especially during particle adhesion and during sintering when grains of different orientation are formed. Initial grain orientation affects final particle morphology leading to exposure of different crystal surfaces that can affect the performance of Au nanoparticles (e.g., catalytic efficiency). Coalescence between crystalline and amorphous nanoparticles of different size results in polycrystalline particles of increasing crystallinity with time and temperature. Crystallinity affects the sintering rate and mechanism. Such simulations of free‐standing Au nanoparticle coalescence are relevant also to Au nanoparticles on supports that do not exhibit strong affinity or strong metal support interactions. © 2015 American Institute of Chemical Engineers AIChE J, 62: 589–598, 2016